Characterization of newly developed high yielding common bean (Phaseolus vulgaris L.) varieties ‘NIFA Lobia Red-22’ and ‘NIFA Lobia Yellow-22’ - Shah, Gul Sanat; Saeed, Iqbal; Ahmad, Shahzad; Mansoor, Muhammad; Wahid, Abdul; Jehan, Aftab (International Journal of Applied and Experimental Biology, 2023)
Common bean (Phaseolus vulgaris L.) improvement program was initiated at Nuclear Institute for Food and Agriculture (NIFA) in 2018. Germplasm from various research institutes and farmers’ fields in KP was collected. The collected germplasm was evaluated in non-replicated fashion in spring 2018 and 2019 at research farm of NIFA for plant type, yield and yield components. Six genotypes were finally selected based on seed color, growth habit and subsequently tested in replicated yield trials conducted at NIFA, Peshawar and on farmers’ fields at Charsadda in spring 2020 & 2021, at Agricultural Research Institute (ARI), Mingora, Swat and Agricultural Research Station (ARS), Chitral in Kharif 2020, and on farmers’ fields at different locations in Kuram in kharif 2020 and 2021. Two genotypes, NCB-Tajaki (NIFA Lobia Red-22) and NCB-Watani (NIFA Lobia Yellow-22) out yielded all other genotypes across all locations as well as seasons. In spring 2020 and 2021, NCB-Tajaki (NIFA Lobia Red-22) and NCB-Watani (NIFA Lobia Yellow-22) produced higher average seed yield of 2195 and 2206 kg ha-1, respectively, whereas in kharif 2020 and 2021, the two genotypes produced higher average seed yield of 2082 and 2075 kg ha-1, respectively compared with other genotypes. The two genotypes were approved by the KP Seed Council under the name NIFA Lobia Red-22 and NIFA Lobia Yellow-22 for general cultivation in common bean growing areas of the KP on 20-01-2022.